2019
DOI: 10.1017/s0033291719001995
|View full text |Cite
|
Sign up to set email alerts
|

An update on the efficacy of anti-inflammatory agents for patients with schizophrenia: a meta-analysis

Abstract: BackgroundAccumulating evidence shows that a propensity towards a pro-inflammatory status in the brain plays an important role in schizophrenia. Anti-inflammatory drugs might compensate this propensity. This study provides an update regarding the efficacy of agents with some anti-inflammatory actions for schizophrenia symptoms tested in randomized controlled trials (RCTs).MethodsPubMed, Embase, the National Institutes of Health website (http://www.clinicaltrials.gov), and the Cochrane Database of Systematic Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
88
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(94 citation statements)
references
References 146 publications
(161 reference statements)
1
88
0
1
Order By: Relevance
“…A recent meta-analysis showed that a variety of medications can reduce the severity of symptoms of schizophrenia. These medications are aspirin (by reducing inflammation by modifying cyclooxygenase-2 enzyme), estrogens (through immunomodulatory effects), minocycline (by inhibiting microglia), and N-acetylcysteine (as an anti-inflammatory agent) (130).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis showed that a variety of medications can reduce the severity of symptoms of schizophrenia. These medications are aspirin (by reducing inflammation by modifying cyclooxygenase-2 enzyme), estrogens (through immunomodulatory effects), minocycline (by inhibiting microglia), and N-acetylcysteine (as an anti-inflammatory agent) (130).…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing literature on the role of anti-inflammatory treatments in individuals with schizophrenia (97)(98)(99). Given the heterogeneity of inflammatory markers in the studies demonstrating relationships with negative symptom severity, blocking inflammation in treatment trials represents a complementary approach to understanding these relationships.…”
Section: Negative Symptoms and Anti-inflammatory Treatment Trialsmentioning
confidence: 99%
“…To add more, investigations revealed, in animal models of psychiatric disorders and in patients, that estrogen and estrogen signaling are disturbed and that they are associated with not only the cognitive deficits but, also, the manifestations of the symptoms, which could also be reversed with estrogen administration or treatments targeting estrogen-signaling pathways [ 11 , 12 , 13 ]. Thus, together with much evidence on estrogen signaling disruptions in psychiatric disorders, recently, their effects have been taken under examination in multiple clinical trials for the critical assessment and evaluation of their efficacy as a new treatment for psychiatric patients [ 14 , 15 , 16 , 17 , 18 ]. Altogether, accumulating evidence suggests that estrogen and estrogen signaling may be highly implicated in the pathophysiology of psychiatric disorders, warranting a comprehensive and integrated understanding of estrogen and estrogen signaling across multiple levels of the brain system architecture from cellular and molecular to systemic to elucidate the mechanisms involved in its therapeutic effects in psychiatric disorders.…”
Section: Introductionmentioning
confidence: 99%